2021
DOI: 10.3762/bjnano.12.81
|View full text |Cite
|
Sign up to set email alerts
|

Criteria ruling particle agglomeration

Abstract: Most of the technically important properties of nanomaterials, such as superparamagnetism or luminescence, depend on the particle size. During synthesis and handling of nanoparticles, agglomeration may occur. Agglomeration of nanoparticles may be controlled by different mechanisms. During synthesis one observes agglomeration controlled by the geometry and electrical charges of the particles. Additionally, one may find agglomeration controlled by thermodynamic interaction of the particles in the direction of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…There is a strict exponential relationship between the particle size and the number of particles. It can be shown that this relationship is related to a maximum of entropy [10,11]. This exponential relation is valid regardless of the number of iterations.…”
Section: Simulation Results Using Monte Carlo Calculations 31 Non-loc...mentioning
confidence: 85%
See 2 more Smart Citations
“…There is a strict exponential relationship between the particle size and the number of particles. It can be shown that this relationship is related to a maximum of entropy [10,11]. This exponential relation is valid regardless of the number of iterations.…”
Section: Simulation Results Using Monte Carlo Calculations 31 Non-loc...mentioning
confidence: 85%
“…Therefore, for these calculations, the particles are not localized; they are just identified by a number. This basic assumption leads to an arrangement characterized by a maximum of entropy, provided that the probability or energy of interaction is neglected [10,11]. As explained in the section 'Theoretical background', this arrangement allows us to consider the interaction between the particles.…”
Section: Simulation Results Using Monte Carlo Calculations 31 Non-loc...mentioning
confidence: 99%
See 1 more Smart Citation